Vietnam antes de la guerra. Desde los orígenes hasta la Batalla de Dien Bien Phu (258 a.C. - 1954) y un epílogo necesario: la década de 1960. - Morón, Camilo (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
Archeology indicates that the Vietnamese come from the fusion of groups that were once south of the Yangtze River and the population that had long settled in the territories of present-day Vietnam. French colonialism (1855-1955) aff ected the traditional structures of Vietnam to their foundations. The social, political, and economic contradictions provided an anti-French sentiment while consolidating a growing nationalism among the Vietnamese. During the 1920s and 1930s, communism began to stoke the fires of nationalist discontent. French colonialism ended with the Battle of Dien Bien Phu in 1954.